Strategi Inovasi Manajemen Perubahan: Membangun Ketangguhan Organisasi di Era Disrupsi - Yudha Hartlanda Martianto; Ari Anggarani Winadi Prasetyoning (Universitas Muhammadiyah Semarang, 2024)
This article discusses innovation strategies in change management to build organizational resilience in an era of disruption. Constant change and technological disruption have driven organizations to develop strong adaptability and innovation capabilities. This research identifies various strategies that can help organizations face change better, as well as the importance of building organizational resilience to remain relevant and competitive amidst current market dynamics. In an era of ever-growing disruption, change management, and innovation are the main keys for organizations that want to survive and develop. By focusing on adaptability, inclusive leadership, risk management, digital transformation, and a culture of innovation, organizations can face complex challenges. Through a targeted and integrated approach, organizations can create a solid foundation to better face future changes. Keywords: Change Management, Innovation, Organizational Resilience, Disruption, Strategy.